Evaluation of Explosiveness of Strength and Power among College Volleyball Players in Ondo, Nigeria - Oluwasogo R. Ojo (West African Journal of Open and Flexible Learning, 2019)
The coaches’ contribution to the effectiveness of a team’s performance is highly influential and players must be well equipped to execute a variety of skills during play. This study, therefore, evaluated the explosiveness of leg strength and leg power of volleyball players at preseason and post season training. Principle of Specificity provided the framework for this study. Thirty college volleyball players (15 males and 15 females) participated in the study. Each player performed on the court season training specifically with squat and vertical jump test. Pretest and posttest measurement were taken. Paired groups type of t-test was used to analyse the data. There was significant difference in the players’ scores for leg strength (LS) (x̅ = 24.80±4.83), conditions (t = -21.78; df=29; p<.05). There was a significant difference in the scores for leg power (LP) (t=-27.38; df=29; p <.05). The results indicated that there were significant differences in LS between males and females (t = 3.557; df = 28; p < .05). The results also indicated that there were significant differences in LP between males and females (t= 8.311; df = 28; p < .05). It was revealed that the training improved their leg strength and leg power. Therefore, coaches should engage volleyball players with exercise drills that would develop the lower body strength and power because they need explosiveness to be more effective to get off the floor quickly and reaching up above the net.